Navigating Adversity: Assessing Teacher Resilience to Challenging Secondary School Environments in Morogoro, Tanzania - Costantine, Edgar; Mwinjuma, Juma Saidi; Nemes, Joyce (Journal of Multidisciplinary Research and Development, 2025)
The study explored teachers’ resilience in challenging environments in Morogoro Municipality using a mixed-methods approach. It combined quantitative data from a resilience scale with qualitative insights from interviews with nine teachers. Findings indicated that many teachers reported low resilience, correlating with issues like high turnover and job dissatisfaction. Teachers expressed a lack of confidence and competence, influenced by socio-economic factors and difficult work conditions. Thematic analysis revealed varied individual experiences of resilience, highlighting the need for supportive school cultures and targeted strategies to enhance teachers' coping abilities. The study advocates for tailored professional development programs addressing teachers’ specific needs, particularly those with low resilience. Recommendations include fostering positive school environments, promoting social support, and improving time management and coping strategies. By focusing on these areas, educational institutions can build a more resilient teaching workforce, benefiting both educators and students. The findings contribute to the broader discourse on teacher resilience, suggesting that systematic support can improve educational outcomes and retention in Morogoro Municipality and beyond.